Development of Transparent Epoxy Resin–Bi₂O₃ Composites as Alternative Radiation Shielding Materials for Optical Shielding - Rizki Rifa'i Majid; Kusnanto Mukti Wibowo; Arga Pratama Rahardian; Fathur Rahman Nugraha; Supriyadi Supriyadi (Jurnal Health Sains, 2026)
Scattered radiation exposure during radiology procedures can reach the head and eye lenses of personnel, requiring eye protection with good radiation attenuation capabilities without compromising comfort. Conventional lead-based radiation protection materials have high density, making them heavy and less ergonomic for long-term use. This study aims to evaluate the X-ray attenuation capability of a transparent epoxy resin–bismuth oxide (Bi₂O₃) composite as a candidate optical shielding material for radiation glasses based on the Half Value Layer (HVL) parameter. The composite was made using epoxy resin as a matrix and Bi₂O₃ as a high atomic number filler, with a mass ratio of 5:1 and a thickness of 0.5 mm and 1.0 mm. Measurements were performed using a diagnostic X-ray machine at voltages of 40 kV and 45 kV with an ionization dosimeter detector. The HVL value was calculated based on the linear attenuation coefficient (μ), and the data were analyzed using the Shapiro–Wilk normality test and Spearman's correlation. The results showed that an increase in composite thickness resulted in an increase in the HVL value, and there was a significant positive correlation between thickness and HVL (r = 0.681; p < 0.01). The epoxy resin–Bi₂O₃ composite showed effective attenuation at thin thicknesses with optical transparency characteristics, making it a potential lead-free optical shielding material for radiation glasses. These findings demonstrate that Bi₂O₃--epoxy resin composites are promising candidates for developing lightweight, transparent, and effective radiation protective eyewear.